APLIKASI RESERVASI KLINIK HEWAN RUMAH CEMONG BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING - Natalia, Hopi; Mulyana, Dadan; Dwicahya Supriatman, Rian (Jurnal Mahasiswa Sistem Informasi Galuh, 2024)
Increasing public awareness of pet welfare drives the growth of the animal health service industry, including the Rumah Cemong Animal Clinic in Ciamis. However, clinics often face challenges such as long queues, long waiting times, limited information, and ineffective manual reservation systems. This study aims to create a web-based animal clinic reservation application to overcome these problems. The research methods include literature studies, interviews, observations, and application creation using the Extreme Programming (XP) method, with system modeling using UML diagrams, the Laravel framework, the PHP programming language, and the MySQL database. System testing is carried out using blackbox testing. The output of this study is a reservation application that improves operational efficiency and pet welfare in animal clinics.